Case report: NUP98::LEDGF fusion gene drives malignant hematological tumor with mixed immunological phenotype - Xue, Song; Chen, Jia-qi; Wang, Tong; Zhang, Li-na; Chen, Man; Sun, Hui-peng (Frontiers in Oncology, 2024)
This is the first report of NUP98::LEDGF positive malignant hematological tumor expressing T cell and myeloid lineage antigens. Patients carrying this fusion gene have a high relapse rate and a poor prognosis, allo-HSCT may be an option to cure this disease. This patient underwent allo-HSCT, a relapse occurred three months post-transplantation. Subsequent screening at our hospital confirmed the presence of the NUP98::LEDGF fusion gene, salvage therapy was administered, followed by a successful second allo-HSCT. Furthermore, we included eight previously reported cases from the literature for analysis and discuss.